High-value compound induction by flashing light in Diacronema lutheri and Tetraselmis striata CTP4. (September 2022) - Schüler, Lisa M.; Walter, Juline M.; Kato, Hidehiko; Suzuki, Hirono; Hulatt, Christopher J.; Rautenberger, Ralf; Navalho, Sofia; Schmid, Benjamin; Varela, João; Kiron, Viswanath; Schulze, Peter S.C.
Abstract: Phototrophic microalgae use light to produce biomass and high-value compounds, such as pigments and polyunsaturated fatty acids (PUFA), for food and feed. These biomolecules can be induced by flashing light during the final growth stage. We tested different exposure times (1–6 days) of flashing light ( f  = 0.5, 5, 50 Hz; duty cycle = 0.05) on biomass, pigment and fatty acid productivity in Diacronema lutheri and Tetraselmis striata . A three-day exposure to low-frequency (5 Hz) flashing light successfully increased the production of fucoxanthin, diatoxanthin, eicosapentaenoic (EPA) and docosahexaenoic (DHA) acids in D. lutheri up to 4.6-fold and of lutein, zeaxanthin and EPA in T. striata up to 1.3-fold compared to that of continuous light. Biomass productivity declined 2-fold for D. lutheri and remained similar for T. striata compared to that of continuous light. Thus, short-term treatments of flashing light may be promising for industrial algal production to increase biomass value. Graphical abstract: Unlabelled Image Highlights: Flashing light in a two-stage approach improves high-value compound productivity. Low-frequency flashing light significantly inhibited growth of D. lutheri . 5 Hz flashing light induced diatoxanthin productivity by 4.6-fold in D. lutheri . 5 Hz flashing light induced carotenoids and EPA by 1.3-fold in T. striata . Algal biomass quality optimized after 3-days low-frequency flashing light treatment.